Islamic Business Entrepreneurs: To Create Excellent, Courageous and Independent Muslim Entrepreneurs - Nursyamsi; dedi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2022)
Abstract. This paper aims to examine Islamic business entrepreneurs in an effort to produce Muslim entrepreneurs who are superior, courageous, and independent. This paper concludes that Islamic Business Entrepreneur is entrepreneurship is all business activities that are carried out commercially in order to produce goods or services in a way that does not conflict with the Shari'a. The foundation of Islamic Business Entrepreneur is the Al-Qur'an and As-Sunnah. The functions of Islamic business entrepreneurs are 1). Seeking success in this world and the hereafter, 2). Provide benefits to other community members, 3). Cultivating a dynamic work and life ethic, as well as increasing community participation in nation building, 4). Develop entrepreneurship and make a major contribution to the expansion of employment opportunities, 5). Reducing unemployment, 6). Increase the country's economic strength.